Revealing the spatio-temporal coupling coordination characteristics and influencing factors of carbon emissions from urban use and ecosystem service values in China at the municipal scale - Zhao, Shuang; Yu, Zhengyong; Liu, Wei (Frontiers in Ecology and Evolution, 2025)
In the context of the “dual-carbon” goal, studying the complex relationship between carbon emissions and ecosystem service values brought about by land-use change is of great significance in promoting regional low-carbon optimization, territorial spatial governance, and the achievement of the goal of carbon peaking and carbon neutrality. This study takes 286 cities in China as the research object, and based on the data of China’s land use and ecosystem service value (ESV) from 2012 to 2022, adopts geo-spatial analysis techniques such as spatial autocorrelation and geographically-weighted regression models to study the spatial and temporal characteristics, the degree of coupling coordination, and the influencing factors of China’s municipal total land use carbon emissions and ESV. The results show that (1) China’s total land-use carbon emissions have exhibited an overall increasing trend from 2012 to 2022. The total ESV has shown a downward trend characterized by an inverted “N” shape. (2) The coupling coordination effect between land-use carbon emissions and ESV in China generally shows a mirrored “L” growth shape. (3) There is a significant spatial negative correlation between land-use carbon emissions and ESV, primarily manifested as “high-high,” “high-low,” and “low-low” clustering characteristics. (4) Three socio-economic factors—local fiscal general budget expenditure, energy utilization efficiency, and total population—positively influence the coupling coordination of land-use carbon emissions and ESV. Strictly controlling the local fiscal general budget expenditure, energy utilization efficiency, and total population can effectively promote China's green, low-carbon development and ecological security.